Comparisons of Daily Behavior Across 21 Countries. (April 2017) - Baranski, Erica N.; Gardiner, Gwen; Guillaume, Esther; Aveyard, Mark; Bastian, Brock; Bronin, Igor; Ivanova, Christina; Cheng, Joey T.; Kock, François S. de; Denissen, Jaap J. A.; Gallardo-Pujol, David; Halama, Peter; et al.
While a large body of research has investigated cultural differences in behavior, this typical study assesses a single behavioral outcome, in a single context, compared across two countries. The current study compared a broad array of behaviors across 21 countries ( N = 5, 522). Participants described their behavior at 7:00 p.m. the previous evening using the 68 items of the Riverside Behavioral Q-sort (RBQ). Correlations between average patterns of behavior in each country ranged from r = .69 to r = .97 and, in general, described a positive and relaxed activity. The most similar patterns were United States/Canada and least similar were Japan/United Arab Emirates (UAE). Similarities in behavior within countries were largest in Spain and smallest in the UAE. Further analyses correlated average RBQ item placements in each country with, among others, country-level value dimensions, personality traits, self-esteem levels, economic output, and population. Extroversion, openness, neuroticism, conscientiousness, self-esteem, happiness, and tolerant attitudes yielded more significant correlations than expected by chance.